2007
DOI: 10.1016/j.exer.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential dependence of regulatory volume decrease behavior in rabbit corneal epithelial cells on MAPK superfamily activation

Abstract: We characterized the dependence of hypotonicity-induced regulatory volume decrease (RVD) responses on mitogen-activated protein kinase (MAPK) pathway signaling in SV40-immortalized rabbit corneal epithelial cells (RCEC). Following calcein-AM loading, RVD was monitored using a microplate fluorescence reader. Western blot analysis determined MAPK activation. After 30 min, the RVD response restored the relative cell volume to nearly isotonic values, whereas it was inhibited when cells were bathed either in a Cl −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Indeed, there is evidence to suggest the involvement of ERK, p38 MAPK, and JNK in control of RVI (285,558,803,854) and RVD (759,1049) in at least some cell types. MAPK activation may also contribute to the volume-dependent reorganization of the actin cytoskeleton (sect.…”
Section: Roles Of Mapks In the Response To Osmotic Volume Perturbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is evidence to suggest the involvement of ERK, p38 MAPK, and JNK in control of RVI (285,558,803,854) and RVD (759,1049) in at least some cell types. MAPK activation may also contribute to the volume-dependent reorganization of the actin cytoskeleton (sect.…”
Section: Roles Of Mapks In the Response To Osmotic Volume Perturbationsmentioning
confidence: 99%
“…Moreover, there are several examples of swelling-induced stimulation of JNK and p38 MAPK activity (e.g., Refs. 624,713,759,993,1049), raising the question of to which extent changes in MAPK activity are part of the volume response per se, as opposed to being general stress responses activated by cell volume perturbations. Finally, a recent study demonstrated that also ERK5 is activated by hyperosmotic stress in fibroblasts and appears to promote cell survival under these conditions by downregulating Fas ligand expression (1067).…”
Section: Mapksmentioning
confidence: 99%
“…Such restoration is in part dependent on activation of Na-K-2Cl 1 co-transporter (NKCC1)-induced osmolyte influx coupled to Na-K pump stimulation [11]. On the other hand, during exposure to a hypotonic challenge, CEC initially swell, and activate a RV decrease (RVD) response to restore their isotonic volume [12]. In human CEC (HCEC), RVD is dependent on increases in K + and Cl − efflux through volume-sensitive ion channels [9,12] and K-Cl cotransporter 1 (KCC1) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Their association in HCEC is requisite for NKCC1 activation and RVI induction [15]. On the other hand, activation of MAPKs ERK and JNK is required for RVD whereas p38 stimulation occurs subsequent to RVD in rabbit CEC (RCEC) [12]. Ca 2+ signaling is critical to induce RVD during exposure to a hypotonic challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation